(untitled) (Journal of Educational Sciences, 2016)
The article is dedicated to one of actual themes of modern society. The problem of professional training perfection of future teachers, renewing the contexts and technology of teaching is a constant object of active investigation and theoretical conceive. At professional training perfection of future teachers the important signifi cance has the using of informational technologies, from one hand, and an effective technology and its application at a teaching process, from the other one. In given work authors consider the role and importance of informational, multimedial technologies, using them in the pedagogical process, as well as their tasks.